2010
DOI: 10.1016/j.biopsych.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Withdrawal Increases Threat-Induced Anxiety but Not Fear: Neuroadaptation in Human Addiction

Abstract: Background-Stress response neuroadaptation has been repeatedly implicated in animal addiction models for many drugs including nicotine. Programmatic laboratory research that examines the stress response of nicotine-deprived humans is necessary to confirm that stress neuroadaptations observed in animal models generalize to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(129 citation statements)
references
References 48 publications
7
122
0
Order By: Relevance
“…Animal neuroscience addiction models suggest that neuroadaptation in the response to uncertain threats and other stressors following repeated, chronic drug use provides one important mechanism in the etiology of alcohol and other drug addiction 8 . Research from our laboratory using these cued threat tasks has provided preliminary support for this etiological mechanism in humans 29,34,44 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Animal neuroscience addiction models suggest that neuroadaptation in the response to uncertain threats and other stressors following repeated, chronic drug use provides one important mechanism in the etiology of alcohol and other drug addiction 8 . Research from our laboratory using these cued threat tasks has provided preliminary support for this etiological mechanism in humans 29,34,44 .…”
Section: Discussionmentioning
confidence: 88%
“…The NPU task manipulates uncertainty regarding both IF (shock probability) and WHEN (shock timing) shocks will occur. The NPU task has been used to examine drug administration and deprivation effects on negative affective response 4,34 and etiological mechanisms in mood and anxiety disorders [22][23][24][41][42][43] . In other research, Curtin and colleagues have also developed variants of these cued threat tasks that precisely manipulate threat uncertainty about WHEN (shock timing) 5,29,44 ; WHERE (administration location on body for shock) 25 ; and HOW BAD (shock intensity) 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine withdrawal induces an increased anxiety state in both human [37][38][39][40][41] and animal models. [42][43][44][45][46] By utilizing three behavioral paradigms known to assess anxiety-like behavior, we found that BDNF Met/Met mice have reduced anxiety-like behavior following nicotine withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Although craving and cognitive impairments are reliable markers of nicotine withdrawal (Kenney and Gould, 2008;Levin et al, 2006;McClernon et al, 2004;Rezvani and Levin, 2001), anxiety has been shown to impact relapse rate as well (Dani and Harris, 2005;DiMatteo et al, 2000). Furthermore, nicotine withdrawal itself induces an increased anxiety state in both human (Dani et al, 2005;Hogle et al, 2010;Picciotto et al, 2002;Piper et al, 2011;Pomerleau et al, 2005) and animal models (Costall et al, 1989;Irvine et al, 2001;Jackson et al, 2008Jackson et al, , 2009Jonkman et al, 2005;Stoker et al, 2008). A recent functional imaging study in smokers correlated affect with aberrant activation in the hippocampus during smoking cue presentation (McClernon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%